2021
DOI: 10.1177/14761270211011703
|View full text |Cite
|
Sign up to set email alerts
|

A call for deep engagement for impact: Addressing the planetary emergency

Abstract: In a world facing catastrophic shocks, there are tremendous opportunities for management scholars to engage and make fundamental contributions to the grand challenges that lie ahead. To do so, our focus must move away from a theory-fetish toward a more applied action orientation that contributes to theory-building but does not make that its main or singular aim. In this paper, we argue, that our field’s primary research aim must not be to see how we can build theory out of a crisis, but rather how our organiza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 25 publications
1
24
0
Order By: Relevance
“…This orientation on the common good, I will argue, presents a different governing logic of interorganisational collaborations that extends longstanding commitments to “appreciative inquiry” (Godwin, 2016) and recent accounts of “relational and psychological pathways” (Gibson, 2022) and “mutualism” (Khanagha et al, 2022). The “common good” as a interorganisational collaboration logic and design framework follows the spirit of Ferraro’s et al (2015) multivocal, participatory architectures, Doh’s et al (2018) call for “collective entrepreneurship” and Williams” and Whiteman’s (2021) call for deep “engagement for impact” as imperative in addressing grand societal challenges and restoring balance in the relationship between science and society (Mintzberg, 2015). It extends these perspectives by positioning inclusiveness as integral to the common good, a hitherto absent dimension of cross-boundary collaborations.…”
Section: Introductionmentioning
confidence: 99%
“…This orientation on the common good, I will argue, presents a different governing logic of interorganisational collaborations that extends longstanding commitments to “appreciative inquiry” (Godwin, 2016) and recent accounts of “relational and psychological pathways” (Gibson, 2022) and “mutualism” (Khanagha et al, 2022). The “common good” as a interorganisational collaboration logic and design framework follows the spirit of Ferraro’s et al (2015) multivocal, participatory architectures, Doh’s et al (2018) call for “collective entrepreneurship” and Williams” and Whiteman’s (2021) call for deep “engagement for impact” as imperative in addressing grand societal challenges and restoring balance in the relationship between science and society (Mintzberg, 2015). It extends these perspectives by positioning inclusiveness as integral to the common good, a hitherto absent dimension of cross-boundary collaborations.…”
Section: Introductionmentioning
confidence: 99%
“…This is in part because realizing the potential of cities and companies lies in first understanding their impact and collective potential for action. Yet consensus is growing that clear scientific guidance to spur and assist more sustainable decision-making and target setting among these actors is needed [16][17][18][19][20] . Most recently, Bai et al (2022) showed that companies with science-based targets for climate aim for more ambitious greenhouse gas (GHG) emissions reductions than companies with climate targets based on other methods, and much higher than national pledges to the Paris Agreement 21 .…”
Section: Mainmentioning
confidence: 99%
“…Tett, 2021), and our impact as scholars (Hoffman, 2021;Walls et al, 2021). In particular, in this special forum, Williams and Whiteman (2021) call for academic research into sustainability issues to be less-possessed with developing new theories, and more focused upon impacting practice. While there is a long history of calling for greater relevance in management studies (e.g.…”
Section: The Role Of the Researchers In 50: The Age Of Radical Sustainabilitymentioning
confidence: 99%
“…We consider this So!apbox Forum as something of a call to arms for strategy and organization scholars. The essays in this forum provoke us to open our thinking about the broader, interdependent systems within which organizations operate (Hahn and Tampe, 2021;Howard-Grenville and Lahneman, 2021), the role of managers within those organizations (Walls et al, 2021), and about our own roles as teachers (Hoffman, 2021) and impacting the participants in our research (Williams and Whiteman, 2021). This is a crucial overarching agenda.…”
Section: Introductionmentioning
confidence: 99%